A novel approach to the diagnosis and treatment of hemoptysis in infants: A case series. Issue 11 (18th September 2018) - Zaidi, S. Javed; Schweig, Lorene; Patel, Dhaval; Javois, Alexander; Akhter, Javeed
Abstract: Introduction: Hemoptysis in children is an uncommon presenting symptom but can be life‐threatening if massive. Cardiac catheterization and coil embolization of aorto‐pulmonary collateral vessels (APCs) is uncommon in pediatric hemoptysis patients without congenital heart disease. Methods: We present a series of seven infants (≤12 months of age) with hemoptysis, all of whom underwent cardiac catheterization to look for and intervene upon APCs, if found. Only those patients who underwent both bronchoscopy as well as cardiac catheterization from January 1995 to January 2015 were included in this retrospective review. Results: Seven patients met inclusion criteria, and three had a history of recurrent hemoptysis. The mean age was 3 months. Four had evidence of bleeding on bronchoscopy. All seven had respiratory distress which necessitated ICU admission; five required mechanical ventilation. Cardiac catheterization showed significant APCs (>2 mm) in six of the seven studied patients, all of which were coil embolized. One patient had no significant APCs and therefore, no embolization. All patients had complete resolution with no recurrences during the 10‐20‐year outpatient follow‐up period. Chest CT scans were not helpful in delineating the site or etiology of bleeding in any patient. Conclusions: APCs should be considered as a differential diagnosis for pulmonary hemorrhage in infants after more common causes have been ruled out.